2009
DOI: 10.3945/jn.108.103853
|View full text |Cite
|
Sign up to set email alerts
|

The Leucine Content of a Complete Meal Directs Peak Activation but Not Duration of Skeletal Muscle Protein Synthesis and Mammalian Target of Rapamycin Signaling in Rats

Abstract: This study examined the impact of leucine (Leu) derived from complete meals on stimulation of skeletal muscle protein synthesis (MPS). Expt. 1 examined time course changes in translation initiation and MPS after a meal. Male rats ( approximately 300 g) were trained for 5 d to eat 3 meals/d providing 20, 50, and 30% of energy from whey protein, carbohydrates, and fats, respectively. Plasma and skeletal muscle were collected at time 0 (baseline) after 12 h of food deprivation and then at 45, 90, 135, 180, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
148
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(168 citation statements)
references
References 22 publications
12
148
2
6
Order By: Relevance
“…On this basis, it would seem unlikely that increasing blood flow per se is responsible for this effect (20); rather it is likely to be a feature of sustained (10) increases in muscle protein turnover (for remodeling/adaptive purposes) and muscle metabolic demand. These data underscore the concept that exercise is required to enhance anabolic responses to nutrition and that this cannot be reproduced by artificially increasing muscle MBV or AA availability, probably due to the "musclefull" effect of AA utilization by muscle for anabolic purposes, at rest (3,9,25), whereby MPS becomes refractory to the stimulatory anabolic effects of nutrition despite continued availability.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On this basis, it would seem unlikely that increasing blood flow per se is responsible for this effect (20); rather it is likely to be a feature of sustained (10) increases in muscle protein turnover (for remodeling/adaptive purposes) and muscle metabolic demand. These data underscore the concept that exercise is required to enhance anabolic responses to nutrition and that this cannot be reproduced by artificially increasing muscle MBV or AA availability, probably due to the "musclefull" effect of AA utilization by muscle for anabolic purposes, at rest (3,9,25), whereby MPS becomes refractory to the stimulatory anabolic effects of nutrition despite continued availability.…”
Section: Discussionmentioning
confidence: 91%
“…Nonetheless, it is recognized that the muscle metabolic background under exercising conditions is distinct from that under postprandial conditions. Finally, recent work has demonstrated that there exist maximum amounts of substrate [ϳ20 g protein (24), ϳ10 g EAA (11,16), doses ϳ3 g of leucine (37,50)] and limited durations of their exposure to muscle [maximum ϳ2 h (3,9,25)], which will stimulate muscle's use of EAA for MPS. However, we conclude that these limits of AA utilization for MPS are unlikely to be due to declining MBV, especially as MBV still remained elevated at the end of the "active" anabolic period.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of leucine is commonly used in animal models to simulate feeding-induced changes in protein synthesis [35][36][37] and to show that sedentary diabetic organisms have impaired protein synthesis rates when compared with control animals [9]. Here we show that a modest amount of aerobic physical activity increases both the basal (fasting) and nutrient-stimulated rates of muscle protein synthesis in severely hyperglycaemic Px animals without an insulin response to feeding.…”
Section: Discussionmentioning
confidence: 65%
“…Previous reports have demonstrated that overnight fasting almost completely reduced the phosphorylation of mTOR downstream targets and subsequent protein synthesis in both skeletal muscle and the liver (16,24,25). In addition, Norton et al showed that peak mTOR signaling responses occur shortly after consumption of a meal (26). Rats were starved for 18 h before the experiment began and dissected 1 and 3 h after Orn administration.…”
Section: Discussionmentioning
confidence: 99%